THÈME : FÉMINISATION DANS L’ENSEIGNEMENT EN PROVINCE ÉDUCATIONNELLE NORD-KIVU II DE 2008-2012 - RUHANGAZA, BAHATI (IJRDO - Journal of Social Science and Humanities Research, 2022)
This investigation is entitled « An ongoing study of the rate of women representativity in assignment of the provincial Education of elementary, primary, secondary and professional teaching North Kivu since 2008 till 2012.Our main preoccupation was to grap rate in our internal and external structures. We aimed at verifying genre equality throughout our investigation period. The documentary approach helped us to get data for the elaboration of this paper.The percentage calculations, the indication of parity, the squared-chi of independence, the analysis of variance with one factor have helped us in analyzing and interpreting our data.After the variance analysis, we have noted that women are actually under presented with in our varials. Among the administrative personnel the indication of parity has been of 100% at the elementary level. The woman under representation has been manifest at primary and secondary school. The man representation is not significantly different at all administrative levels.